The Effect Of Using Running Text Media Towards Students’ Reading Comprehension At The Eleventh Grade Students Of SMAN 5 Mandau - Devia Mutiara Sari (Jolly Journal of English Education, 2025)
This study was carried out find out The Effect Of Using Running Text Media Toward Student’s Reading Comprehension at The Eleventh Grade Students of SMAN 5 Mandau.”. The descriptive quantitative was applied to describe data, with a quasi-experimental research design. The study population was all 164 students in grade XI consisting of 5 classes. Due to the large population, the researcher  took a sample of 64 students using cluster random sampling technique. In this study, the average pre-test score for the experimental class was 51.25 and the control class was 50.62. Meanwhile, the average post-test score of the experimental class was 74.69 and the control class was 63.75. Based on the probability scores gathered from SPSS 22, it was shown that the sig. (2-tailed) value for Pair 1 was 0.000 < 0.05. This indicated that there were significant differences in the average students’ reading comprehension between the pre-test and post-test. This meant that the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected.